Field Performance and Molecular Evaluation of Micropropagated Strawberry - Nirmal Mandal1; Prakash Kanti Das2, Saikat Gantait1* (Recent Research in Science and Technology, 2010)
Micropropagated and conventionally propagated plantlets of strawberry (Fragaria Ã— ananassa Duch. cv. Chandler) were transferred to the similar field condition and growth stage. A comparative study was conducted based on morphological parameters as well as genetic assessments using ISSR markers. The in vitro generated strawberry plants exhibited significantly vigourous morphological growth and earlier flower induction when compared to the plants propagated through planting of runners. Genetic assessment through ISSR showed no polymorphism in banding pattern and thus it was revealed that, there was no significant variation between micropropagated and conventional propagated plants at molecular level.Â